1996
DOI: 10.1042/bj3160713
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the type of divalent cation, Ca2+ or Mg2+, bound at the high-affinity site and of the ionic composition of the solution on the structure of F-actin

Abstract: F-actins containing either Ca2+ or Mg2+ at the single high-affinity site for a divalent cation differ in their dynamic properties [Carlier (1991) J. Biol. Chem. 266, 1-4]. In an attempt to obtain information on the structural basis of this difference, we probed the conformation of specific sites in the subunits of Mg- and Ca-F-actin with limited proteolysis by subtilisin and trypsin. The influence of the kind of polymerizing salt was also investigated. At high proteinase concentrations required for digestion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
44
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 54 publications
6
44
0
Order By: Relevance
“…The intercept value of K polym extrapolated to 1M cation is related to the intrinsic binding free energy of an actin subunit and associated cation with a filament end (27,28). These values are not identical for all cations evaluated, suggesting that filaments assembled with different cationic species have variable thermodynamic stabilities and salt-dependent conformational distribution(s) (6,7,20,29,30).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The intercept value of K polym extrapolated to 1M cation is related to the intrinsic binding free energy of an actin subunit and associated cation with a filament end (27,28). These values are not identical for all cations evaluated, suggesting that filaments assembled with different cationic species have variable thermodynamic stabilities and salt-dependent conformational distribution(s) (6,7,20,29,30).…”
Section: Resultsmentioning
confidence: 99%
“…The actin C c and (monomer and filament) conformation depend on the nucleotide-associated divalent cation (Ca 2þ or Mg 2þ ) as well as the type and concentration of ions in solution (6,7,(13)(14)(15), a behavior shared among characterized actins and their bacterial homologs (16). However, it is not firmly established if these salt effects on actin filament assembly and mechanics originate from nonspecific ion effects (e.g., electrostatic screening, counterion condensation, etc.)…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The susceptibility of the D-loop to subtilisin cleavage between residues Met-47 and Gly-48 has been commonly used to monitor conformational changes in the D-loop resulting from factors such as the type of nucleotide and divalent cation bound to actin (32,33), and the binding of actin-depolymerizing factor (ADF)/ cofilin to the filament (34). We found that phosphorylation of Tyr-53 protects the D-loop from subtilisin cleavage, as shown by a Ϸ50% reduction in the initial rate of cleavage of the D-loop in pY53-actin compared to unphosphorylated actin (Fig.…”
Section: Probing the Structures Of Py53-actin And Unphosphorylated Acmentioning
confidence: 99%
“…Therefore, a slow degradation of the alanine-and serine-rich segment 227-235 in subdomain 4 (56, 57) results in fragmentation of the F-actin subunits into the N-terminal 30-kDa peptide (residues 1-227) and 16-kDa C-terminal peptide (residues 235-375). The faint 33-kDa band is a product of subtilisin cleavage between Leu 67 and Lys 68 (57). Digestion of subtilisin-modified F-actin (Fig.…”
Section: Figmentioning
confidence: 99%